Acoustic Traces of Poetry in South Asia. Issue 3 (3rd July 2019) - Pue, A. Sean
Abstract: Taking advantage of the appropriateness of computational analysis for complex patterns, this essay considers how computational humanities methods can move beyond semantic meaning and the written word to address oral forms of performance and aural forms of recognition of South Asian poetry. The essay focuses on two significant figures in the history of modern "Urdu-Hindi" poetry, the contemporary poet Fahmida Riaz and the pre-Partition poet Miraji. Through computational metrical detection and visualization, it considers how poetic meter operates in their work and addresses their audiences in creative ways in their varied milieus. Through a contextualized elaboration of these literary figures' work, as well as a modeling of their poetic forms, these methods expose the way that sound and rhythm carries meaning in their poetry.